Understanding Online Loan Intentions: The Roles of Risk Perception, Financial Literacy, and Debt Management - Andriyani, Ameliya; Supira, Wita; Fadillah, Arum Nur; Kurniawati, Melati Sabrina (Lentera Ilmu Nusantara, 2025)
The rapid growth of digital financial platforms, particularly online loans, has created an urgent need to understand the behavioral factors that influence borrowing decisions in the digital era. This study aims to analyze the effect of risk perception on interest in making online loans with financial literacy as a mediating variable and debt management as a moderating variable. The background of the study is based on the increasing use of digital lending services that have not been balanced with adequate financial understanding and the results of previous studies that show inconsistency. The method used is a quantitative approach with a survey technique on 100 respondents, and the data was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3.0. The results of the study indicate that risk perception does not have a direct and significant effect on interest in making online loans, but has a significant positive effect on financial literacy. Financial literacy has been shown to significantly increase interest in online loans and mediate the relationship between risk perception and borrowing interest, although the mediation effect is not statistically significant. Meanwhile, debt management does not provide a significant moderating effect on the relationship. These findings indicate that financial literacy is a key factor in forming rational financial decisions amidst digital risks. The practical implication is that online loan providers need to integrate financial education and debt management features to encourage wiser and more responsible borrowing behavior.